Development of Cognitive Training Program With EEG Headset - Zhipeng Huang (IEEE Access, 2019)
Recent research has shown that cognitive function can be improved with proper practices. To improve cognitive skills, we developed a series of training programs using the Unity 3DTMGame Engine, which connects to an EPOC+ headset from EMOTIVTMto provide EEG data. In order to engage participants and maintain interest, we employed game concepts and developed each program as a game with specific rules and three levels of difficulty. The programs focus on such cognitive abilities as reaction speed, flexibility, attention span, memory and problem solving. We analyzed a user's performance with a detection system embedded in each program; the system automatically directs the user to a suitable level. To simplify software development, the interactive framework was designed as an application programming interface (API), which employs rich texts, static images, animations, and user interactions. We also investigated the effectiveness of using cognitive training with EPOC+ headsets to improve cognitive skills. The results are promising in some users.